1983
DOI: 10.1083/jcb.96.5.1197
|View full text |Cite
|
Sign up to set email alerts
|

The rough endoplasmic reticulum and the Golgi apparatus visualized using specific antibodies in normal and tumoral prolactin cells in culture.

Abstract: Antibodies directed against membrane components of dog pancreas rough endoplasmic reticulum (A-RER) and rat liver Golgi apparatus (A-Golgi) (Louvard, D., H. Reggio, and G. Warren, 1982, J. Cell Biol. 92:92-107) have been applied to cultured rat prolactin (PRL) cells, either normal cells in primary cultures, or clonal GH3 cells. In normal PRL cells, the A-RER stained the membranes of the perinuclear cisternae as well as those of many parallel RER cisternae. The A-Golgi stained part of the Golgi membranes. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
2
23
1
Order By: Relevance
“…After perfusion fixation, the PT was removed and postfixed in the same fixative without glutaraldehyde overnight at 4t. The tissue samples were subjected to electron microscopic immunocytochemistry by a modification of the pre-embedding method described by ToUGARD et al (1983). From fixed samples of the PT attached by the hypothalamus, 40um-thick frontal sections through the region of the PT were made with a microslicer (Dosaka EM Co., Ltd. Japan).…”
Section: Electron Microscopic Immunocytochemistrymentioning
confidence: 99%
“…After perfusion fixation, the PT was removed and postfixed in the same fixative without glutaraldehyde overnight at 4t. The tissue samples were subjected to electron microscopic immunocytochemistry by a modification of the pre-embedding method described by ToUGARD et al (1983). From fixed samples of the PT attached by the hypothalamus, 40um-thick frontal sections through the region of the PT were made with a microslicer (Dosaka EM Co., Ltd. Japan).…”
Section: Electron Microscopic Immunocytochemistrymentioning
confidence: 99%
“…We also review previously reported data concerning two types of intracellular antigens including 1) the subcellular localization of the secretory product, prolactin, in normal and tumor cells (Tougard et al, 1980a(Tougard et al, ,b, 1982; and 2) the subcellular localization of membrane components in intracellular compartments involved in the process of secretion and endocytosis (Tougard et al, 1983(Tougard et al, , 1985. These immunocytochemical results are discussed in relationship to others in the literature concerning this field.…”
Section: Introductionmentioning
confidence: 77%
“…The secretory granule membrane remained completely un stained [37], Antibodies against two components of the secretory granule membrane of rat endocrine pancreas were recently obtained and stained specifically, by im munofluorescence, small structures in normal rat islets of Langerhans, anterior pituitary and adrenal medulla [33]. Antibodies against synaptophysin, a 38-kd integral membrane glycoprotein of synaptic vesicles [35,36], stained by immunofluorescence some small vesicles in anterior pituitary, adrenal medulla [38] and in GH3 cells [39], Recent findings [40,41] raised the possibility of the presence of a small amount of synaptophysin in the membrane of secretory granules of adrenal medulla.…”
Section: Membrane Compartments Involved In the Secretory Pathwaymentioning
confidence: 99%
“…Using polyclonal antibodies against some RER mem brane antigens and a 135-kd Golgi membrane antigen [28], we have clearly discriminated without any overlap ping between the two compartments in PRL cells in cul ture [37], The antibodies against the RER antigens stained the membrane of all RER cisternae, including the perinuclear cisterna whereas the antibodies against the Golgi membrane antigen stained the membrane of a Golgi subcompartment (medial to trans saccules). The secretory granule membrane remained completely un stained [37], Antibodies against two components of the secretory granule membrane of rat endocrine pancreas were recently obtained and stained specifically, by im munofluorescence, small structures in normal rat islets of Langerhans, anterior pituitary and adrenal medulla [33].…”
Section: Membrane Compartments Involved In the Secretory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation